An Association between BK Virus Replication in Bone Marrow and Cytopenia in Kidney-Transplant Recipients. (29th April 2014) - Pambrun, Emilie; Mengelle, Catherine; Fillola, Geneviève; Laharrague, Patrick; Esposito, Laure; Cardeau-Desangles, Isabelle; Del Bello, Arnaud; Izopet, Jacques; Rostaing, Lionel; Kamar, Nassim
Abstract : The human polyomavirus BK (BKV) is associated with severe complications, such as ureteric stenosis and polyomavirus-associated nephropathy (PVAN), which often occur in kidney-transplant patients. However, it is unknown if BKV can replicate within bone marrow. The aim of this study was to search for BKV replication within the bone marrow of kidney-transplant patients presenting with a hematological disorder. Seventy-two kidney-transplant patients underwent bone-marrow aspiration for cytopenia. At least one virus was detected in the bone marrow of 25/72 patients (35%), that is, parvovirus B19 alone ( n = 8), parvovirus plus Epstein-Barr virus (EBV) ( n = 3), cytomegalovirus ( n = 4), EBV ( n = 2), BKV alone ( n = 7), and BKV plus EBV ( n = 1). Three of the eight patients who had BKV replication within the bone marrow had no detectable BKV replication in the blood. Neutropenia was observed in all patients with BKV replication in the bone marrow, and blockade of granulocyte maturation was observed. Hematological disorders disappeared in all patients after doses of immunosuppressants were reduced. In conclusion, an association between BKV replication in bone marrow and hematological disorders, especially neutropenia, was observed. Further studies are needed to confirm these findings.